RADIOLARIAN SKELETONS: FORMATION AND MORPHOLOGY OF SKELETAL SHELLS - Afanasieva M.S. (My University, 2006)
A new scheme of successive stages in the formation of radiolarian skeletons is proposed. Successive complication of symmetry patterns is considered. The morphology and evolutionary changes of five types of skeletal shells, i.e., latticed, reticulate, spongy, porous, and lamellar, are analyzed. © Pleiades Publishing, Inc. 2006.
Keywords: RADIOLARIA; SKELETON FORMATION; TYPESOF SYMMETRY